GENETIC DIVERSITY OF HEPATITIS C AND GENDER PREDISPOSITION: A CROSS-SECTIONAL STUDY - Amer, Khan; Maryam, Samia; Wajeeha, Amer (Pakistan Journal of Physiology, 2018)
Background: Hepatitis C is becoming a very common infection in Pakistan. Treatment in the past was partially effective and carried a lot of side effects. Different antiviral regimens are effective in different genotypes. Knowledge of prevalent genotypes is very important not only in treatment, but to design future strategies as well. This study was conducted to see different prevalent genotypes in a semi-controlled group along with their association with gender. Methods: This cross-sectional analytical study was carried out at Gastroenterology Department of Combined Military Hospital Lahore from Sep 2016 to Mar 2017. Non-probability consecutive sampling technique was used to recruit 568 patients coming to Gastroenterology OPD with positive Anti HCV and HCV-RNA PCR. Patients having signs of decompensation were excluded. Results: There were 297 (52.2%) male and 271 (47.7%) female patients with mean age 48.1Â±32 years.Genotype 1 was seen in 27 (4.8%), genotype 3 in 524 (92.3%), genotype 3 and 4 in 14 (2.5%), 2 and 3 in 1 (0.2%), and genotype was un-typeable in 2 (0.4%) cases. Genotype 1 and combined 3 and 4 were more frequent in males while genotype 3 was more common in females (p=0.007). Conclusion: Genotype 3 is the predominant hepatitis genotype in our population. Genotype 1 is more common in males whereas genotype 3 is more common in females. Pak J Physiol 2018;14(1):37â€“9